NATURAL WEAPON AGAINST DENGUE: LARVICIDAL EFFICACY OF PAPAYA (Carica Papaya L.) FRUIT PEEL ETHANOL EXTRACT ON AEDES ALBOPICTUS - Nidha Luthfiana Fawziah; Nur Mahdi; Andi Zsaza Rafiatul Muklis; Deni Setiawan (DSM Publisher, 2025)
Dengue or, as it is commonly known, dengue fever, has become a public health problem in the world, not only in Indonesia. Until now, dengue disease is still not well controlled. Dengue fever is caused by Aedes argypi and Aedes albopictus mosquitoes. The purpose of this study was to determine the effectiveness of papaya peel extract (Carica papaya L) against Aedes albopictus mosquito larvae. This study is an experimental study of post test only control group design using 600 Aedes albopictus larvae. This study used papaya peel extract with 6 concentration treatment groups of 0.4 mg/ml, 0.8 mg/ml, 0.12 mg/ml, 0.16 mg/ml, positive control group and negative control group. Observations were made 24 hours after treatment and larval mortality was calculated every 1 hour. The results showed that the average larval mortality at a concentration of 0.4 mg/ml was 6.25%, concentration of 0.8 mg/ml was 8.25%, concentration of 0.12 mg/ml was 10.75%, at a concentration of 0.16 mg/ml was 14.5%, for the positive control was 100%, and for the negative control was 0%. The results of probit analysis of LC90 of papaya peel extract amounted to 48.501 and LT50 at the fastest killing concentration of 0.16 mg/ml was 59.017 hours. Based on the results of the study, it can be concluded that papaya peel extract (Carica papaya L.) can kill Aedes albopictus mosquito larvae.